Fifth Five Year Plan Andhra Pradesh (1974-75 to 1978-79) Draft Outline Part II Sectoral Programmes - Planning Commission (Planning Commission, 1972)
In Andhra Pradesh, about 70% of the people are dependent on agriculture and this percentage will continue to be high in spite of industrialisation in the immediate future. As pointed out in the Fatioral Approach, the main attack on poverty will have to be ok. rural poverty. If, therefore, the standard of living of vas$ majority of our people is to be raised, the basic priority in our developmental programmes will still have to be accorded to Agriculture.
Planning and Co-Operation Department Government of Andhra Pradesh
Planning and Co-Operation Department Government of Andhra Pradesh
Keywords: Agriculture and Allied Programmes; Community Development & Cooperation; Irrigation & Power; Industry And Mining; Transport and Communications; Social Services; Information And Publicity; Welfare of Scheduled Tribes